Meningkatkan Motorik Anak Melalui Kegiatan Wall Climbing di Al-Kindi Preschool Pangkalpinang - Qomariah, Nurul; Haria, Haria (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2021)
Early in life, there are several aspects of development that should be stimulated. One of which is that of motor development. The development of a child's motor is vital to note because it affects and supports other developments. To enhance child growth, at al-kindi preschool pangkalpinang is done through wall climbing activity. The purpose of this activity is to train a child's muscles and to exercise a child's agility in climbing, which will support the other child's motor activities in various activities. It is a descriptive qualitative study. The data gathered is obtained through three data-collection techniques interview, observation, and documentation. The results of the study indicate that children's motor development has been enhanced following the limbing of wall activity. This is judged by the increased ability of the child in coordinating hands, feet and eyes when climbing, the child is able to balance the body, be able to hold strong rock points and be able to do wall climbing activities.